The Effect of The Jigsaw Type Cooperative Learning Model Integrated with The Mind Mapping Technique on The Motivation and Learning Outcomes of Elementary School Students in Grade V - Farkhan Nur Mahdi; Akhmad Junaedi (Jurnal Penelitian Pendidikan IPA, 2025)
This study examined the effect of the Jigsaw cooperative learning model integrated with Mind Mapping techniques on fifth-grade students' motivation and learning outcomes at Kalisegoro Elementary School. Using a quasi-experimental design with non-equivalent control groups, 46 students were divided into experimental (n = 23) and control (n = 23) groups. The experimental group received instruction through the Jigsaw cooperative learning model integrated with Mind Mapping, while the control group was taught using an interactive lecture method. Data were collected through cognitive tests and motivation questionnaires. Results showed significant improvements in both groups' learning outcomes (p < 0.05), with the experimental group demonstrating greater gains (mean increase from 65.57 to 84.17) compared to the control group (55.30 to 71.13). The Mann-Whitney U test confirmed significant differences between groups (p = 0.004) with an effect size of r = 0.42 (medium effect). Similarly, learning motivation increased more substantially in the experimental group (68.09 to 76.70) than the control group (66.04 to 73.87), with a significant difference between groups (p = 0.001) and an effect size of Cohen's d = 0.163 (small effect). The findings suggest that the Jigsaw cooperative learning model with Mind Mapping effectively enhances both motivation and learning outcomes in elementary school science education.